T cell Regulatory Plasmacytoid Dendritic Cells Expressing Indoleamine 2,3 Dioxygenase - Kahler, David J. (Handb Exp Pharmacol, 2009)
Mature dendritic cells (DCs) are potent stimulators of T cells that recognize antigens presented by the DCs. In this chapter we describe mature DCs that suppress T cell responses to antigens they present due to expression of the intracellular enzyme indoleamine 2,3 dioxygenase (IDO). IDO-competent DCs are a subset of plasmacytoid DCs that can be induced to express IDO under certain inflammatory conditions in humans and mice. Though rare, IDO-expressing DCs acquire potent T cell suppressor activity that may predominate over the T cell stimulatory functions of all other antigen-presenting cells in physiologic environments due in part, to cooperation with regulatory T cells. Thus, IDO-expressing DCs are critical regulators of adaptive immunity that contribute to a wide range of inflammatory disease processes. As such, manipulating IDO expression in DCs using IDO inhibitors or IDO inducers offers considerable opportunities to improve immunotherapies in a range of clinically-significant disease syndromes.